A 5 GHz narrow‐beam leaky‐wave antenna using binomially distributed slot based substrate integrated waveguide. Issue 9 (11th August 2018) - Farooq, Memoona; Khan, Muhammad U.; Cheema, Hammad M.
Abstract: This article presents a planar substrate integrated waveguide based leaky wave antenna (LWA) with narrow beamwidth, high directivity, and low side lobe levels (SLL). Through first‐time use of binomially distributed slots, a significant decrease in SLL along with a small form factor is achieved. Designed on a Rogers 5880 substrate, the proposed design occupies 250 × 45 mm 2 exhibiting a beamwidth of 11.3 ° and sidelobe level less than −10 dB at 5.6 GHz. In comparison with conventional LWA with uniform slots, a 63% size reduction is also achieved.